2015
DOI: 10.1155/2015/791498
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sickle Cell Disease: A Review for Physician Education in Nigeria (Sub-Saharan Africa)

Abstract: Sickle cell disease (SCD) predominates in sub-Saharan Africa, East Mediterranean areas, Middle East, and India. Nigeria, being the most populous black nation in the world, bears its greatest burden in sub-Saharan Africa. The last few decades have witnessed remarkable scientific progress in the understanding of the complex pathophysiology of the disease. Improved clinical insights have heralded development and establishment of disease modifying interventions such as chronic blood transfusions, hydroxyurea thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 165 publications
(221 reference statements)
5
138
1
6
Order By: Relevance
“…Therefore, patients can develop both conditions simultaneously. Patients who have sickle cell/β-thalassemia typically have symptoms similar to sickle cell anemia, though the intensity of the anemia can vary depending on the severity of the thalassemia [12]. Increased research in population genetics of hematological disorders over the past few years have enabled better understanding of the genetic factors responsible for progression and severity of anemia in Hb E/β-thalassemia [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients can develop both conditions simultaneously. Patients who have sickle cell/β-thalassemia typically have symptoms similar to sickle cell anemia, though the intensity of the anemia can vary depending on the severity of the thalassemia [12]. Increased research in population genetics of hematological disorders over the past few years have enabled better understanding of the genetic factors responsible for progression and severity of anemia in Hb E/β-thalassemia [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above factors, there is small evidence that the SCD genotype is associated with STA, since the frequency of this complication is high in patients who have hemoglobin SC and Hbs-ß [6,26]. Accordingly, studies suggest that the HLA haplotype of DRB1 *130101-DQB1* 060101 has been shown to be strongly associated with the development of STA when compared to other [27].…”
Section: Acute Thoracic Syndromementioning
confidence: 99%
“…As a result, red blood cells are prone to fail and agglutinate in states of low oxygen saturation. A range of complications arising from this condition may occur, such as chronic hemolytic anemia resulting from the premature removal of red blood cells from the circulation, vaso-occlusion caused by erythrocytic deposition in small vessels or bifurcations, increased blood viscosity, predisposition to primary and recurrent infections In addition to advanced stage organ failure [2,6,7]. The occurrence of such events is correlated with the propensity to develop a serious complication, the acute thoracic syndrome (STA).…”
Section: Introductionmentioning
confidence: 99%
“…In corroboration of this, Alege [2] posited that Nigeria has the largest population of people with sickle cell disease in the world with over 150,000 babies born with serious condition every year. Nigeria bears the greatest burden of sickle cell in Sub-Saharan Africa (Adewoyin) [3] with forty million people carrying the gene for sickle cell disease in the country (Alhassan) [4]. Sickle cell disease can be in several forms which include sickle cell anaemia (when inherited in homozygous state), sickle cell beta plus thalassemia, sickle beta zero thalassemia and others (Adewoyin).…”
Section: Introductionmentioning
confidence: 99%